Perancangan Sistem Informasi Pemesanan Jasa Wedding Organizer Berbasis Web di Ranni Gallery Palembang - Nabila Putri Mareta; Andreo Yudertha; Heru Kurniawan (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
Ranni Gallery is a business engaged in the service sector, which provides wedding equipment. The business process at Ranni Gallery still uses a lot of manual methods causing inefficiency in ordering, it is not uncommon for schedules to clash, double bookings, and slow and error-prone price calculations. Manual ordering that requires customers to come directly causes an increase in costs and time efficiency because 60% of customers come from distant villages. The absence of monthly reports also made it difficult to monitor transactions and business development. A platform is needed to streamline Ranni Gallery’s business, reduce customer dissatisfaction, and minimize errors in calculations, schedules, and monthly reports, namely with a wedding organizer service booking information system. The method used in developing this system is the waterfall waterfall model, using the PHP programming language laravel framework, and designing using the UML (Unifed Modeling Languange) model. Based on the results of blackbox testing, all functions in this system run as expected. Meanwhile, based on the results of UAT testing, this wedding organizer service booking information system obtained a percentage result of 93% which proved that this system was well received by users.